Using electronic marketing methods to achieve cultural and sporting adaptation in companies owning clubs - Mohamed, Mohamed alyasddik (International Journal of Psychosocial Rehabilitation, 2025)
The study aims to Using electronic marketing methods to achieve cultural and sporting adaptation in companies owning clubs. the following conclusions can be concluded: The electronic marketing policy adopted in the companies (under discussion) is marred by many deficiencies and weaknesses, where the most important manifestations of deficiencies and weaknesses are in the following aspects:The marketing policy adopted is not commensurate with global variables, technological developments and cultural differences due to the following considerations: Individuals are selected based on practical experience without regard to cultural diversity and the ability to accept a new culture. In light of the results reached, the researcher was able to present some recommendations that contribute to achieving cultural adaptation in companies owning sports clubs and increasing the use of e-marketing, as shown as follows: The companies owning sports clubs should go towards educating their employees to benefit from them in the electronic marketing process. The selection and employment of individuals should be based on effective performance, multilingualism, appropriate cultural awareness, and sufficient flexibility to accept a new culture because it contributes significantly to the success of the e-marketing process.